Correlation Analysis between the Characteristics of Helicobacter pylori Resistance and the Antibiotic Use Density in a Hospital from 2012 to 2018 - Chenglin Ru (Hindawi Limited, 2021)
Objective. To explore the correlation between the resistance characteristics of Helicobacter pylori (HP) and antibiotic use density (AUD) in a hospital from 2012 to 2018. Methods. HP strains isolated from Chinese PLA General Hospital from 2012 to 2018 were collected to analyze the drug resistance of clarithromycin, levofloxacin, amoxicillin, and metronidazole, and their correlation with the AUD of the outpatient department and inpatient department was analyzed, respectively. Results. From 2012 to 2018, metronidazole-resistant strains accounted for the largest proportion, followed by clarithromycin and levofloxacin, and amoxicillin-resistant strains accounted for the least. In 2012–2018, the resistance rate of clarithromycin, levofloxacin, amoxicillin, and metronidazole has basically increased year by year; from 2012 to 2018, the highest outpatient AUD in a hospital was amoxicillin, followed by clarithromycin and levofloxacin, metronidazole was the lowest, and the inpatient AUD from high to low was levofloxacin, metronidazole, amoxicillin, and clarithromycin. The drug resistance rate of HP in the hospital from 2012 to 2018 was positively correlated with the AUD of clarithromycin (r = 0.884, P=0.017) and levofloxacin (r = 0.934, P=0.002) in the outpatient department. Conclusions. Helicobacter pylori has the strongest resistance to metronidazole and the worst resistance to amoxicillin in the hospital from 2012 to 2018, being related to the intensity of clarithromycin and levofloxacin in the outpatient department. It may provide certain reference significance for the clinical treatment of Helicobacter pylori.